The impact of depression and culture on responses to intrusive autobiographical memories: Cognitive appraisals, cognitive avoidance, and brooding rumination. (31st July 2019) - Mihailova, Stella; Jobson, Laura
Abstract : Objectives: Those with depression ascribe more negative appraisals to intrusive autobiographical memories and use maladaptive strategies to regulate intrusive memory distress. However, it is unknown whether these patterns extend to East Asian samples. This study investigated the influence of culture and depression on intrusive remembering. Design: The study used a 2 (group: European Australian, East Asian) × 2 (depression: depressed, control) cross‐sectional design, with an online intrusive memory diary. Methods: European Australian ( n = 46) and East Asian ( n = 45) participants living in Australia, with and without depression, reported two intrusive memories in real‐time and completed self‐report measures indexing their appraisals of the memories, and their use of cognitive avoidance and brooding rumination in response to the memories. Results: East Asian participants reported significantly greater negative, control, and responsibility appraisals than European Australian participants. Regardless of cultural group, depressed participants endorsed greater maladaptive memory appraisals and brooding compared to controls. Additionally, among East Asian participants, those with depression cognitively avoided memories significantly more than controls. When comparing the two depressed groups, East Asians reported significantly greater brooding and avoidance in response to intrusive memories than Australians. Conclusions: The findings suggest that depression may be associated with some similar maladaptive responses to intrusive autobiographical memories across cultural groups. Clinical interventions targeting unhelpful responses may, therefore, be beneficial for those with depression, regardless of cultural background. Practitioner points: Across both European Australian and East Asian cultures, depressed participants endorsed higher maladaptive intrusive memory appraisals and brooded more in response to memories. Clinical interventions targeting appraisals and emotion regulation in response to intrusive memories may be beneficial for those with depression across both cultural groups. Language and acculturation may have impacted findings, as measures were administered in English and in Australia. Replication using a cross‐country design and larger sample would be beneficial to confirm findings.